Up‐regulation of SPINT2/HAI‐2 by Azacytidine in bone marrow mesenchymal stromal cells affects leukemic stem cell survival and adhesion. Issue 2 (28th November 2018) - Roversi, Fernanda Marconi; Cury, Nathalia Moreno; Lopes, Matheus Rodrigues; Ferro, Karla Priscila; Machado‐Neto, João Agostinho; Alvarez, Marisa Claudia; dos Santos, Gabriela Pereira; Giardini Rosa, Renata; Longhini, Ana Leda; Duarte, Adriana da Silva Santos; Pericole, Fernando Vieira; Favaro, Patricia; et al.
Abstract: The role of tumour microenvironment in neoplasm initiation and malignant evolution has been increasingly recognized. However, the bone marrow mesenchymal stromal cell (BMMSC) contribution to disease progression remains poorly explored. We previously reported that the expression of serine protease inhibitor kunitz‐type2 (SPINT2/HAI‐2), an inhibitor of hepatocyte growth factor (HGF) activation, is significantly lower in BMMSC from myelodysplastic syndromes (MDS) patients compared to healthy donors (HD). Thus, to investigate whether this loss of expression was due to SPINT2/HAI‐2 methylation, BMMSC from MDS and de novo acute myeloid leukaemia (de novo AML) patients were treated with 5‐Azacitidine (Aza), a DNA methyltransferase inhibitor. In MDS‐ and de novo AML‐BMMSC, Aza treatment resulted in a pronounced SPINT2/HAI‐2 levels up‐regulation. Moreover, Aza treatment of HD‐BMMSC did not improve SPINT2/HAI‐2 levels. To understand the role of SPINT2/HAI‐2 down‐regulation in BMMSC physiology, SPINT2/HAI‐2 expression was inhibited by lentivirus. SPINT2 underexpression resulted in an increased production of HGF by HS‐5 stromal cells and improved survival of CD34 + de novo AML cells. We also observed an increased adhesion of de novo AML hematopoietic cells to SPINT2/HAI‐2 silenced cells. Interestingly, BMMSC isolated from MDS and de novo AML patients had increased expression of the integrins CD49b, CD49d, and CD49e. Thus, SPINT2/HAI‐2 may contribute to functional and morphological abnormalities of the microenvironment niche and to stem/progenitor cancer cell progression. Hence, down‐regulation in SPINT2/HAI‐2 gene expression, due to methylation in MDS‐BMMSC and de novo AML‐BMMSC, provides novel insights into the pathogenic role of the leukemic bone marrow microenvironment.